2018
DOI: 10.5009/gnl17515
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-Occluded Retrograde Transvenous Obliteration versus Transjugular Intrahepatic Portosystemic Shunt for the Management of Gastric Variceal Bleeding

Abstract: Background/AimsGastric varices (GVs) are a major cause of upper gastrointestinal bleeding in patients with liver cirrhosis. The current treatments of choice are balloon-occluded retrograde transvenous obliteration (BRTO) and the placement of a transjugular intrahepatic portosystemic shunt (TIPS). We aimed to compare the efficacy and outcomes of these two methods for the management of GV bleeding.MethodsThis retrospective study included consecutive patients who received BRTO (n=157) or TIPS (n=19) to control GV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…In the setting of gastric varices, BRTO has been reported to achieve comparable or even better results than TIPS in terms of immediate bleeding control (96.2% vs 84.2%), rebleeding-free survival rate (38.6% vs 23.4%, adjusted HR 0.34, p = 0.001) and overall survival rates at 5 years (38.5% vs 34.4%, adjusted HR 0.44, p = 0.01) (Gimm et al 2018). Complete obliteration of gastric fundal varices has been achieved in as high as 91% of cases, with successful complete obliteration translating to rebleed-free survival, and none of the patients experiencing a worsening of their Child-Pugh score (Hiraga et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of gastric varices, BRTO has been reported to achieve comparable or even better results than TIPS in terms of immediate bleeding control (96.2% vs 84.2%), rebleeding-free survival rate (38.6% vs 23.4%, adjusted HR 0.34, p = 0.001) and overall survival rates at 5 years (38.5% vs 34.4%, adjusted HR 0.44, p = 0.01) (Gimm et al 2018). Complete obliteration of gastric fundal varices has been achieved in as high as 91% of cases, with successful complete obliteration translating to rebleed-free survival, and none of the patients experiencing a worsening of their Child-Pugh score (Hiraga et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80][81] However, ascites and hepatic hydrothorax may significantly worsen, similar to EVs, due to an increase in portal pressures after taking down the gastrorenal shunt during BRTO. 82 There have been few comparisons between BRTO and ECI, but in the small series reported, these modalities have comparable rates of initial hemostasis with slightly better long-term rebleeding rates in the BRTO group. 83 In a metaanalysis comparing TIPS and BRTO for the management of GVs, there were no significant differences in initial hemostasis rates or procedure-related complications, but BRTO had less rebleeding and encephalopathy in the long term.…”
Section: Definitive Therapy Of Bleeding From Gastric and Ectopic Varimentioning
confidence: 90%
“…For patients, a long survival time is the most valuable benefit. Gimm et al reported that the postprocedure OS after 5 years was longer after BRTO than after TIPS [27]. Ninoi et al reported that among patients in Child-Pugh class A, Total (95% CI) Total events Heterogeneity: tau 2 = 0.00; chi 2 = 2.95, df = 4 (P = 0.57); I 2 = 0% Figure 2: Meta-analysis results: (a) overall survival rate, (b) haemostasis rate, (c) rebleeding rate, (d) hepatic encephalopathy rate, (e) aggravated ascites rate, (f ) technical success rate, and (g) Child-Pugh change.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-one articles were removed after finding duplicates. e full texts of thirty-one records were read, and nine [24][25][26][27][28][29][30][31][32] met the inclusion criteria ( Figure 1): one RCT and eight cohort studies. e specific details of the papers that were included in our study are displayed in Table 2.…”
Section: Studies Retrieved and Characteristicsmentioning
confidence: 99%